Quantificação de fluxos hídricos em pavimentos altamente permeáveis na mitigação de inundações urbanas - Pazetti, Caroline Francisca (2021)
The growth of urbanization leads to an increase in impermeable surfaces and, consequently, changes in the hydrological cycle, for example, an increase in surface runoff (Roff). The increase in Roff can overload the rain drainage systems and, consequently, increase the risk of urban flooding. To mitigate the problems of volume and peak surface runoff, Sustainable Drainage Systems (SuDS) are being increasingly used. Permeable Pavements (PP) are an example of SuDS and allow rainwater infiltration and storage. However, there are few experimental studies on the hydrological performance of PP in Brazil. The aim of this study is to quantify water fluxes in an experimental plot of highly permeable PP. The experimental area is located in the municipality of Pato Branco, Paraná. The aim of this study is to quantify water fluxes in an experimental plot of highly permeable PP. The study was carried out on a plot scale (experimental) and the PP was built with the presence of a bottom drain and a porous and permeable interlocking concrete block lining. Twelve rainfall events were monitored and evaluated between January and May 2021, in addition to data on drained water in the experimental module. The evaluation of the peak flow behavior was made in relation to the precipitation heights and the antecedent humidity (AMC). The PP module had an average percentage of 65.89% of the volumes. The PP module had an average percentage of 65.89% of the volumes drained in relation to the precipitated volumes, thus demonstrating that the PP performance was consistent, without the occurrence of runoff (Roff). The results indicate that events with AMC III approached rainfall volumes, and events with AMC I moved away from precipitation volumes. The results of this study contribute to increase the credibility in the use of PP, especially in southern Brazil. In addition, the results open the possibility of calibrating computational models of sustainable rainwater drainage. drained in relation to the precipitated volumes, thus demonstrating that the PP performance was consistent, without the occurrence of runoff (Roff). The results indicate that events with AMC III approached rainfall volumes, and events with AMC I moved away from precipitation volumes. The results of this study contribute to increase the credibility in the use of PP, especially in southern Brazil. In addition, the results open the possibility of calibrating computational models of sustainable rainwater drainage.